Bioengineered bacterial outer membrane vesicles encapsulated Polybia–mastoparan I fusion peptide as a promising nanoplatform for bladder cancer immune-modulatory chemotherapy - Ren, Chunyu; Li, Yangyang; Cong, Zhaoqing; Li, Zhuoran; Xie, Leiming; Wu, Song (Frontiers in Immunology, 2023)
Background: Nanosized bacterial outer membrane vesicles (OMVs) secreted by Gram-negative bacteria have emerged as a novel antitumor nanomedicine reagent due to their immunostimulatory properties. The encapsulated bacterial composition in OMVs can be edited via manipulating bioengineering technology on paternal bacteria, allowing us to design an ingenious antitumor platform by loading Polybia-mastoparan I (MPI) fusion peptide into OMVs. Methods: OMVs containing MPI fusion peptide were obtained from bioengineered Escherichia coli transformed with recombinant plasmid. The antitumor efficacy of bioengineered OMVs in vitro was verified by performing cell viability, wound-healing and apoptosis assays using MB49 and UMUC3 cells, respectively. Subcutaneous MB49 tumor bearing mice were involved to investigate the tumor inhibition ability of bioengineered OMVs. Besides, the activated immune response in tumor and the biosafety were also evaluated in detail. Results: The resulted OMVs had the successful encapsulation of MPI fusion peptides and were performed physical characterization for morphology, size and zeta potential. Cell viabilities of bladder cancer cells including MB49 and UMUC3 rather than a non-carcinomatous cell line (bEnd.3) were decreased when incubated with bioengineered OMVs. In addition, bioengineered OMVs restrained migration and induced apoptosis of bladder cancer cells. With intratumor injection of bioengineered OMVs, growths of subcutaneous MB49 tumors were significantly restricted. The inherent immunostimulation of OMVs was demonstrated to trigger maturation of dendritic cells (DCs), recruitment of macrophages and infiltration of cytotoxic T lymphocytes (CTLs), resulting the increased secretion of pro-inflammatory cytokines (IL-6, TNF-α, and IFN-γ). Meanwhile, several evidences also indicated bioengineered OMVs had satisfactory biosafety. Conclusion: Bioengineered OMVs fabricated in present study were characterized by strong bladder cancer suppression and great biocompatibility, providing a new avenue for clinical bladder cancer therapy.